2013
DOI: 10.1016/j.ypmed.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sitting time and a range of symptoms in mid-age women

Abstract: ObjectiveTo explore longitudinal associations between sitting and physical and psychological symptoms in mid-age women. Method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…This may be particularly true for the generic sitting time measure. However, previous ALSWH analyses have shown associations between this sitting measure with body weight, breathing difficulty and chest pain, and mortality, 15,17,33 and other studies have demonstrated relationships with mortality using similar generic measures. 16 Notwithstanding, misclassification may have resulted in underestimation of the true effect of sitting time on health-related costs.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This may be particularly true for the generic sitting time measure. However, previous ALSWH analyses have shown associations between this sitting measure with body weight, breathing difficulty and chest pain, and mortality, 15,17,33 and other studies have demonstrated relationships with mortality using similar generic measures. 16 Notwithstanding, misclassification may have resulted in underestimation of the true effect of sitting time on health-related costs.…”
Section: Discussionmentioning
confidence: 63%
“…15 Hours spent sitting on a weekday and a weekend day were then averaged ([weekday × 5 + weekend day × 2]/7) to estimate the mean sitting time in hours/day, and categorized in approximate tertiles, while 6 accounting for adverse health outcomes being reported at around 8 hours/day: low=0−4 hours/day, moderate=5−7 hours/day, or high=≥8 hours/day. 8,9,16,17 Physical Activity…”
Section: Sitting Timementioning
confidence: 99%
See 1 more Smart Citation
“…Three studies found that people who spent more time watching television and/or using the computer had a greater likelihood of having mental disorders (de Wit, van Straten, Lamers, Cuijpers, & Penninx, 2011;Peeters et al, 2012;Sanchez-Villegas et al, 2008), and two studies found that people that spent more time engaging in television, computer, and/or screen-based entertainment behaviours tended to have more psychological distress (Hamer et al, 2010) and worse mental wellbeing (Atkin, Bull, & Biddle, 2012). This previous research is limited in that it remains unclear if the link to mental health is with the overall time spent sitting or the time spent in a specific context (i.e., television-watching, using the computer, screen-based entertainment).…”
Section: Sitting and Mental Healthmentioning
confidence: 99%
“…In epidemiological research, SB is often analysed in categories, for example tertiles. 51,66,67 Despite the limited accuracy when used as a continuous measure, the SQ has acceptable agreement for categorising participants into tertiles (for both average day and weekday).…”
Section: Discussionmentioning
confidence: 99%